Voices of the Girls : Crossing the Barriers Between Youth, Gender, and Poverty - Cesilini, Sandra; Martin, Lisandro; Aberg, Caroline (World Bank, Washington, DC, 2012)
The primary strategic goal of the World Bank's civil society team for Latin America and the Caribbean is to promote inclusive governance. Governance is understood as the sum of the many ways that individuals and institutions, public and private, manage their common affairs. It includes formal institutions and regimes empowered to enforce compliance, as well as informal arrangements that people and institutions perceive to be in their interest. The inclusion of a wide range of social actors in the public debate and the promotion of inclusive civic participation is vital to this strategy. Capacity building, aimed at the most vulnerable actors is an essential prerequisite. This brief includes the following headlines: listening to development priorities from the ground: the objectives of the 'voices of the girls'; activities of the 'voices of the girls'; lessons learned; looking ahead; notes; and about the authors.